Heterologous expression of xylanase II from Aspergillus usamii in Pichia pastoris - Zhou, Chenyan (Array, 2009)
Summary: To efficiently produce xylanase for food processing industry, a gene encoding xylanase II (XynII) from Aspergillus usamii has been cloned into the vector pPIC9K and integrated into the genome of Pichia pastoris KM71 by electroporation. By means of minimal dextrose (MD) plates and PCR, the recombinant P. pastoris strains (His+Muts) have been obtained. Activity assay and SDS-PAGE demonstrate that XynII was extracellularly expressed in P. pastoris with the induction of methanol. In shake flask culture, the xylanase activity was up to 1760 U/mL, with the specific activity of 3846.83 U/mg. The optimal pH and temperature of the recombinant XynII were pH=4.0 and 50 °C, respectively. The xylanase was stable below 50 °C and within pH=3.0–5.0. The molecular mass of the recombinant protein was estimated to be 21 kDa by SDS-PAGE. This enzyme had Km of 4.55 mg/mL, vmax of 15.15 mM/s and kcat of 455 s–1. Its activity was increased by EDTA and Ca2+ ions, but strongly inhibited by Mn2+ and Fe2+ ions. This is the first report demonstrating the possibility of mass production of A. usamii protein using P. pastoris